Der Neo-Fisher-Effekt: Die historische Alternative zur Nullzinspolitik - Bertram Schefold (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2019)
Die Europäische Zentral Bank hat am 6. Juni 2019 beschlossen, die Nullzinspolitik bis Mitte 2020 beizubehalten, obwohl mit dieser das Inflationsziel von 2% seit Jahren, in Japan seit Jahrzehnten, verfehlt wird. Nach dem Neo-Fisher-Effekt sollte, gegeben dieses Ziel, der Zins nicht gesenkt, sondern gehoben werden, weil die Inflationsrate der Differenz von Nominal- und langfristig stabilem Realzins entspricht. Zwar senken rasche Zinserhöhungen Nachfrage und Preise, aber daraus folgt nicht notwendig, dass niedrige Zinsen die Nachfrage anregen. Gemäß neueren Untersuchungen werden langsam durchgeführte Zinserhöhungen bei rationalen Erwartungen dagegen das Preisniveau heben. Der Aufsatz untersucht die begleitenden Verteilungswirkungen und stützt die These mit Überlegungen aus dem 19. Jahrhundert, wonach die gestiegenen Preise durch die Erhöhung der Zinskosten erklärt werden können. – – The European Central Bank decided on 6th June 2019 to retain the zero interest policy at least up to the middle of 2020, although the target of an inflation of 2% has been missed for years, in Japan for decades. Given the target, one should not lower, but increase the rate of interest according to the Neo-Fisher-Effect, since the rate of inflation corresponds to the difference between the nominal and the real interest rate, and the latter seems to be stable in the long run. It is true that rapid increases of the rate of interest depress demand and prices, but it does not follow that low interest rates necessarily stimulate demand. Raising the rate of interest leads according to more recent investigations to higher levels of prices, if the increase is slow and if rational expectations prevail. The paper investigates the accompanying effects on distribution and provides additional reasons for the inflationary effect of rising interest rates by arguing, in line with 19th century considerations, that increased interest costs explain the rise of prices.
urn:nbn:de:hebis:30:3-507397
Keywords: 330; Inflation; Geldpolitik; Europäische Zentralbank; Zinsen